Synthetic inhibitors of snake venom enzymes: Thioesters derived from 2-sulfenyl ethylacetate (2019)
ABSTRACT: Snakebite envenomings are a global public health issue. The therapy based on the administration of animal-derived antivenoms has limited efficacy against the venom-induced local tissue damage, which often leads to permanent disability. Therefore, there is a need to find inhibitors against toxins responsible for local damage. This work aimed to synthesize thioesters derived from 2-sulfenyl ethylacetate and to evaluate the inhibitory effects on two snake venom toxins. Ethyl 2-((4-chlorobenzoyl)thio)acetate (I), Ethyl 2-((3-nitrobenzoyl)thio)acetate (II) and Ethyl 2-((4-nitrobenzoyl)thio)acetate (III) were synthesized and spectroscopically characterized. Computational calculations were performed to support the study. The inhibitory capacity of compounds (I–III) was evaluated on a phospholipase A2 (Cdcum6) isolated from the venom of the Colombian rattlesnake Crotalus durissus cumanensis and the P-I type metalloproteinase Batx-I isolated from Bothrops atrox. I–III inhibited PLA2 with IC50 values of 193.2, 305.4 and 132.7 μM, respectively. Otherwise, compounds II and III inhibited the proteolytic activity of Batx-I with IC50 of 2774 and 1879 μM. Molecular docking studies show that inhibition of PLA2 may be due to interactions of the studied compounds with amino acids in the catalytic site and the cofactor Ca2+. Probably, a blockage of the hydrophobic channel and some amino acids of the interfacial binding surface of PLA2 may occur.